2016
DOI: 10.1016/j.jor.2015.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Is it necessary to embolise all spinal metastases from primary renal tumours?

Abstract: IntroductionSpinal metastases develop in 5-10% of all cancer patients, 1 and renal carcinoma metastases are associated with increased intraoperative blood loss relative to other tumour types. 2 Current studies suggest that as many as 83% of these metastases are hypervascular on angiographic studies. 3 Current best practice guidelines on the management of metastatic renal carcinoma suggest that, prior to any operative intervention on the metastatic deposits, they should undergo pre-operative embolisation to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…3 However, aggressive spinal surgery could be complicated by massive intraoperative hemorrhage in hypervascular osseous metastases. Related studies have demonstrated that preoperative transarterial embolization might reduce intraoperative blood loss, [4][5][6][7][8][9] especially for pathologies prone to hypervascular metastases such as thyroid carcinoma, renal cell carcinoma, and hepatocellular carcinoma. However, not all metastases from such tumors are hypervascular, 5,10 and metastases from other tumor pathologies could be hypervascular as well.…”
mentioning
confidence: 99%
“…3 However, aggressive spinal surgery could be complicated by massive intraoperative hemorrhage in hypervascular osseous metastases. Related studies have demonstrated that preoperative transarterial embolization might reduce intraoperative blood loss, [4][5][6][7][8][9] especially for pathologies prone to hypervascular metastases such as thyroid carcinoma, renal cell carcinoma, and hepatocellular carcinoma. However, not all metastases from such tumors are hypervascular, 5,10 and metastases from other tumor pathologies could be hypervascular as well.…”
mentioning
confidence: 99%